Mifepristone Treatment during Early Adolescence Fails to Restore Maternal Deprivation-Induced Deficits in Behavioral Inhibition of Adult Male Rats - Kentrop, Jiska; van der Tas, Liza; Loi, Manila; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Joëls, Marian; van der Veen, Rixt (Frontiers in Behavioral Neuroscience, 2016)
Early life adversity has a profound impact on brain development and later life health. Animal models have provided insight how early life stress programs stress responsiveness and might contribute to the development of psychiatric disorders. In the present study, the long-term effects of maternal deprivation on behavioral inhibition and attention were examined in adult male Wistar rats. To this end animals were tested in the 5-choice serial reaction time task (5-choice SRTT). We also explored the potential of a 3-day treatment with the glucocorticoid receptor antagonist mifepristone during early adolescence to normalize putative behavioral effects of early life stress. Deprivation of the mother for 24h on postnatal day (PND) 3 led to a modest but significant increase in premature responses in the 5-choice SRTT, but did not affect measures of attention. Bodyweight was lower in deprived animals from weaning until the start of testing. Early adolescent mifepristone treatment (PND 26-28) did not influence performance on the 5-choice SRTT and did not mitigate the deprivation-related impairment in behavioral inhibition. Our results indicate that maternal deprivation leads to impaired behavioral inhibition, and that mifepristone treatment during early adolescence does not normalize the behavioral changes caused by early life stress.